2006
DOI: 10.1016/j.joca.2005.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Early post-traumatic osteoarthritis-like changes in human articular cartilage following rupture of the anterior cruciate ligament

Abstract: These observations reveal that joint instability resulting from ACL injury rapidly results in degenerative changes characteristic of those seen in idiopathic OA at arthroplasty and in experimental OA following ACL surgery. These changes may contribute to the development of post-traumatic OA that is commonly observed following ACL injury. The observations support and extend conclusions from other studies on human and animal articular cartilage and synovial fluids post-ACL injury that have revealed a rapid onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 22 publications
6
101
1
6
Order By: Relevance
“…The development of OA is associated with high-impact sports, which supports the idea that mechanical stress is a major initiator of OA (2). Initially, loss of proteoglycans and of collagen network integrity occur (3). Decreased chondrocyte density and cell death have now been accepted as hallmarks of OA and have also been suggested as causal factors in the initiation of cartilage degradation (4,5).…”
mentioning
confidence: 77%
“…The development of OA is associated with high-impact sports, which supports the idea that mechanical stress is a major initiator of OA (2). Initially, loss of proteoglycans and of collagen network integrity occur (3). Decreased chondrocyte density and cell death have now been accepted as hallmarks of OA and have also been suggested as causal factors in the initiation of cartilage degradation (4,5).…”
mentioning
confidence: 77%
“…Also it is possible that our dilution methodology, especially when aspirating joint fluid from a normal joint, could have altered the true levels of degradative products and enzymes in our study. In contrast to most other studies analyzing synovial fluid where experimental aspirates are compared with aspirates from different, ''healthy'' control patients, the authors chose to compare the uninjured and injured knees from the same patient to account for any potential biomarker elevation resulting from acute systemic trauma [21,26,30,42,43] . With the patient in the supine position, it is difficult to obtain synovial fluid from the normal knee because the fluid likely collects along the posterior capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to look specifically at the presence of proteolytic enzymes after traumatic injury, several authors have shown elevated MMPs and aggrecan degradation after ACL tear. However, the time from ACL injury to joint aspiration had considerable variability in these studies [5,7,26,30]. There are currently no human studies of which we are aware that quantify the concentrations of MMPs and/or aggrecan degradation acutely after articular fracture.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that women have increased incidence of anterior cruciate ligament (ACL) injuries and that these injuries lead to future osteoarthritis regardless of gender [20,21]. ACL injury often results in a characteristic bone bruise on both the lateral femoral condyle and lateral tibia plateau as demonstrated on MRI.…”
Section: Causes Of Knee Osteoarthritis In Womenmentioning
confidence: 99%